ANALISIS HARGA POKOK PRODUKSI DALAM PENETAPAN HARGA JUAL PRODUK - Sisilia Eku; Sultan Syah; Diah Ayu Gustiningsih (Tangible Journal, 2021)
The purpose of this study was to determine and analyze the process of calculating the cost of production and determining the selling price of products on D’strawberry café using the Cost Plus Pricing method full costing mud approach. the research used was a quantitative method with an intrinsic case study. The source of the data obtained was primary data. The analytical method used is the Cost Plus Pricing method. The data collection techniques are interviews (oral, written, electronic media) and observation. The results of this study indicate that there are differences in the process of determining the cost of production and determining the selling price of products between D’strawberry café and the Cost Plus Pricing method. Based and the cost of raw materials plus the expected margin while the selling price determination uses the Cost Plus Pricing method based on the total cost of both production costs and non-production. Cost-plus the expected margin is the reason D’strawberry café does not involve factory overhead costs in the calculation on the cost of production and pricing selling because factory overhead costs are charged to the guest's house business. Keywords : Price Sales, Cost Plus Pricing, And Full Costing